Atheroma Progression in Obese Early-stage Diabetic Japanese Patients in Response to Glycemic Control: Sub-analysis from the DIANA Study - Yoshimasa, Yasunao; Kimura, Kazuo; Miyazaki, Shunichi; Kosuge, Masami; investigators, DIANA study; Sase, Kazuhiro; Kataoka, Yu; Yasuda, Satoshi; Miyamoto, Yoshihiro (Journal of Atherosclerosis and Thrombosis, 2015)
Aim: Diabetes is accompanied by abdominal obesity, which produces various metabolic abnormalities. While metabolic factors have been considered to promote the development of coronary atherosclerosis in the early-stage of diabetes, it remains unknown whether the presence of obesity in early-stage diabetics affects the natural history of coronary atherosclerosis. We herein investigated the characteristics of the disease substrate in obese early-stage diabetics. Methods: The DIANA (DIAbetes and diffuse coronary NArrowing) study was a serial evaluation of angiographic disease progression in early-stage diabetics with coronary artery disease. A total of 252 study subjects were stratified into non-obese (n=168) and obese groups (n=84). Obesity in Japanese subjects was defined as a body mass index ≥25 kg/m2 according to the statement about Japanese obesity from the Japan Society for the Study of Obesity. Coronary atherosclerotic changes were evaluated by a quantitative computed analysis. The total lesion length (TLL=total length of all atherosclerotic lesions) was compared between the groups. Results: The obese patients were younger (p=0.0002) and had higher levels of fasting (p=0.002) and postprandial insulin (p=0.01), and higher triglyceride levels (p=0.02). On serial angiographic evaluations, obese patients had greater disease progression, reflected by a larger percent change in the TLL (24.7±13.7 vs. 7.4±10.0%, p=0.04). However, the improvement of abnormal glucose tolerance was associated with a slowing of disease progression in both non-obese (−0.9±10.7 vs. ＋15.0±11.2%, p=0.04) and obese (＋4.2±22.8 vs. ＋55.5±26.5%, p=0.005) patients. Conclusions: Obese patients with early-stage diabetes exhibit profound disease progression. Glycemic control attenuated the progression of their coronary atherosclerosis. Our findings indicate progressive but modifiable disease in obese early-stage diabetics under optimal glycemic management.